Analisis Kelayakan Integrated Digital Forensics Investigation Framework Untuk Investigasi Smartphone - Ruuhwan Ruuhwan; Imam Riadi; Yudi Prayudi (Universitas Atma Jaya Yogyakarta, 2016)
Abstract. The handling of digital evidence each and every digital data that can proof a determination that a crime has been committed; it may also give the links between a crime and its victims or crime and the culprit. How to verify a valid evidence is to investigate using the approach known as the Digital Forensic Examination Procedures. Integrated Digital Forensic Investigation Framework (IDFIF) is the latest developed method, so that it is interesting to further scrutinize IDFIF, particularly in the process of investigation of a smartphone. The current smartphone devices have similar functions with computers. Although its functions are almost the same as the computer, but there are some differences in the process of digital forensics handling between computer devices and smartphones. The digital evidence handling process stages need to overcome the circumstances that may be encountered by an investigator involving digital evidence particularly on electronic media and smartphone devices in the field. IDFIF needs to develop in such a way so it has the flexibility in handling different types of digital evidence.Keywords: digital evidence, IDFIF, investigation, smartphone Abstrak. Penanganan bukti digital mencakup setiap dan semua data digital yang dapat menjadi bukti penetapan bahwa kejahatan telah dilakukan atau dapat memberikan link antara kejahatan dan korbannya atau kejahatan dan pelakunya. Cara pembuktian untuk mendapatkan bukti valid adalah dengan melakukan investigasi dengan pendekatan Prosedur Pemeriksaan Digital Forensic. Integrated Digital Forensics Investigation Framework (IDFIF) merupakan metode terbaru sehingga IDFIF ini menarik untuk diteliti lebih lanjut terutama dalam proses investigasi smartphone. Saat ini perangkat smartphone memiliki fungsi yang sama dengan komputer. Meskipun demikian, ada beberapa perbedaan dalam proses penanganan digital forensics diantara perangkat komputer dan smartphone. Tahapan proses penanganan barang bukti digital seharusnya dibuat untuk mengatasi keadaan umum yang mungkin dihadapi oleh investigator yang melibatkan barang bukti digital terutama pada perangkat smartphone dan media elektronik terkait di lapangan. IDFIF perlu dikembangkan sehingga memiliki fleksibilitas dalam menangani berbagai jenis barang bukti digital. Kata Kunci: bukti digital, IDFIF, investigasi, smartphone